2018
DOI: 10.1016/j.ibror.2018.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Remote tissue conditioning is neuroprotective against MPTP insult in mice

Abstract: HighlightsRemote tissue conditioning is an emerging neuroprotective strategy.Remote ischemic conditioning and remote photobiomodulation were tested in MPTP mice.Both interventions protected the midbrain against MPTP insult.Combining the interventions yielded no added benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…In a series of experiments on Parkinson's disease, Stone, Johnstone, Mitrofanis and colleagues have shown that neuroprotection against Parkinsonian MPTP insult (in mice) can be achieved with PBM delivered to areas of the body remote from the brain. 36,[171][172][173][174] This abscopal effect of PBM is postulated to be due to immune cells, stem cells, or a circulating (unidentified) mediator. The possibility exists that this mediator is linked to changes in the microbiome.…”
Section: Mechanisms Of Action Of Pbm On the Microbiomementioning
confidence: 99%
“…In a series of experiments on Parkinson's disease, Stone, Johnstone, Mitrofanis and colleagues have shown that neuroprotection against Parkinsonian MPTP insult (in mice) can be achieved with PBM delivered to areas of the body remote from the brain. 36,[171][172][173][174] This abscopal effect of PBM is postulated to be due to immune cells, stem cells, or a circulating (unidentified) mediator. The possibility exists that this mediator is linked to changes in the microbiome.…”
Section: Mechanisms Of Action Of Pbm On the Microbiomementioning
confidence: 99%
“…In mice administered MPTP following sub-chronic or chronic injection schedules, transcranial PBM significantly mitigates the loss of dopaminergic cells in the SNc [11,12,13,14,15,16,17,18], astrogliosis in the SNc and CPu [11] and locomotor deficits as assessed by the open field test [13,15,16,17]. Furthermore, light irradiation of the body (remote PBM) but not the head significantly mitigates the loss of SNc dopaminergic cells in mice exposed to 50 mg/kg MPTP [12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the possibility that PBM therapy targeted at a remote tissue (e.g., abdominal tissue) might elicit systemic mechanisms that provide neuroprotection of the brain is of great interest to researchers [ 83 , 110 , 111 ]. Today, there are a number of convincing examples of the possible systemic effects of PBM in animal models of AD [ 112 , 113 ] and PD [ 74 , 114 , 115 ]. Although the mechanisms underlying the phenomenon of systemic or indirect effects of PBM are not clear, we propose that the effect of PBM on the lymphatic system could be one of them.…”
Section: Pbm Therapymentioning
confidence: 99%